CNS embryonal tumours: WHO 2016 and beyond. (20th February 2018) - Pickles, J. C.; Hawkins, C.; Pietsch, T.; Jacques, T. S.
Abstract : Embryonal tumours of the central nervous system (CNS) present a significant clinical challenge. Many of these neoplasms affect young children, have a very high mortality and therapeutic strategies are often aggressive with poor long‐term outcomes. There is a great need to accurately diagnose embryonal tumours, predict their outcome and adapt therapy to the individual patient's risk. For the first time in 2016, the WHO classification took into account molecular characteristics for the diagnosis of CNS tumours. This integration of histological features with genetic information has significantly changed the diagnostic work‐up and reporting of tumours of the CNS. However, this remains challenging in embryonal tumours due to their previously unaccounted tumour heterogeneity. We describe the recent revisions made to the 4th edition of the WHO classification of CNS tumours and review the main changes, while highlighting some of the more common diagnostic testing strategies.